2023
DOI: 10.1039/d2nr06745e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient thin-film perovskite solar cells from a two-step sintering of nanocrystals

Abstract: Creating semiconductor thin films from sintering of colloidal nanocrystals (NCs) represents a very important technology for high throughput and low cost thin-film photovoltaics. Here we report the creation of all-inorganic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…24,25 CsPbBr 3 bulk film was fabricated from a careful design of sintering process of the CsPbBr 3 -NC film because typical solution deposition methods were of difficulty to adapt for the direct construction of bulk CsPbBr 3 devices (Figure S2). 26 Figure 1b−g shows scanning electronic microscopy (SEM) images of the perovskite-NC and bulk films together with corresponding distribution analysis of the grain size, which are well consistent with evolution of the optical absorption and photoluminescence (PL) spectra in Figure 1h,i.…”
Section: ■ Results and Discussionsupporting
confidence: 75%
“…24,25 CsPbBr 3 bulk film was fabricated from a careful design of sintering process of the CsPbBr 3 -NC film because typical solution deposition methods were of difficulty to adapt for the direct construction of bulk CsPbBr 3 devices (Figure S2). 26 Figure 1b−g shows scanning electronic microscopy (SEM) images of the perovskite-NC and bulk films together with corresponding distribution analysis of the grain size, which are well consistent with evolution of the optical absorption and photoluminescence (PL) spectra in Figure 1h,i.…”
Section: ■ Results and Discussionsupporting
confidence: 75%
“…Since the cmcm phase is more stable than the γ-phase, this path would be a possible perovskite degradation path. More recently, Zhou et al obtained a 2D flake phase when the black CsPbBr 3 was heated via a one-pot synthesis method . By comparing the experiment XRD with the simulation XRD, we found that this phase would be the cmcm phase.…”
Section: Resultsmentioning
confidence: 71%
“…More recently, Zhou et al obtained a 2D flake phase when the black CsPbBr 3 was heated via a one-pot synthesis method. 29 By comparing the experiment XRD with the simulation XRD, we found that this phase would be the cmcm phase. Thus, the perovskite degradation in CsPbBr 3 may follow this mechanism.…”
Section: Phase Transition Pathway Of γ-Cspbi 3 Degradationmentioning
confidence: 92%
“…Combination of sequential low and high temperature annealing resulted in CsPbBr 3 film without pores and impurity phases. 74…”
Section: Other Solution Methodsmentioning
confidence: 99%
“…Since prolonged sintering in high temperature could generate unwanted impurities such as PbCO 3 , a two‐step‐sintering process was adopted to precisely eliminate organic ligands and control the film morphology while minimizing damage to the perovskite. Combination of sequential low and high temperature annealing resulted in CsPbBr 3 film without pores and impurity phases 74 …”
Section: Various Manufacturing Strategies For Cspbbr3 Solar Cellsmentioning
confidence: 99%